Analisis Faktor yang Mempengaruhi Puchase Decision Sunscreen Spray Skintific Pada Generasi Z Di DKI Jakarta - Angelita, Putri Rotua; Monoarfa, Terrylina; Daru Putri Kusumaningtyas (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
This study aims to examine the factors influencing the purchase decision of Skintific sunscreen spray among Generation Z in DKI Jakarta. The research investigates the impact of product innovation, social media marketing, and influencer credibility on consumer purchasing behavior. A quantitative research method was employed, using a survey distributed online to 149 Generation Z respondents who are familiar with or have used Skintific sunscreen spray. The data were analyzed using descriptive statistics and inferential analysis with multiple linear regression. The results reveal that social media marketing and influencer credibility have a significant positive influence on purchase decisions, while product innovation does not show a significant effect. These findings suggest that persuasive communication strategies through social platforms and credible influencers are more influential for Generation Z than product novelty itself. This study provides theoretical contributions to marketing literature and practical insights for skincare brands to enhance their promotional strategies in digital environments.